Impact of Aging and Cognition on Hearing Assistive Technology Use - Jorgensen, Lindsey E.; Messersmith, Jessica J. (Seminars in Hearing, 2015)
Many factors go into appropriate recommendation and use of hearing assistive technology (HAT). The aging auditory system presents with its own complications and intricacies; there are many types of age-related hearing loss, and it is possible that the underlying cause of hearing loss can significantly impact the recommendations and performance with HATs. The audiologist should take into consideration peripheral and central auditory function when selecting HATs for the aging adult population as well as when selecting appropriate types of technology including personal sound amplification products, hearing aids, cochlear implants, and other assistive technology. The cognitive ability of the patient plays a central role in the recommendations of HAT. It is possible that the use of HATs could mitigate some of the effects of cognitive decline and thus should be considered as early as possible. Assessment of ability and appropriate recommendations are crucial to consistent use of HAT devices.
Keywords: Hearing loss; hearing aids; cochlear implants; hearing assistive technology; cognition; adults